2012 North American Power Symposium (NAPS) 2012
DOI: 10.1109/naps.2012.6336316
|View full text |Cite
|
Sign up to set email alerts
|

Investigating performance of numerical distance relay with higher sampling rate

Abstract: This paper investigates the impact on operating time delay and relay maloperation i.e. selectivity, when high sampling rate is used in numerical distance protection (NDP). Simulation is carried out in an on-line way, for different source to line reach impedance ratio (SIR), fault type, fault locations and for different loading conditions. The voltage and current signals from capacitive voltage transformers and current transformers respectively are fed to the numerical distance relay (NDR). Sampling rate of 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In earlier literature by Venkatesh and Swarup (2012), a total of 16, 24, 32 and 64 samples per cycle of the fundamental frequency (50 Hz) are considered to investigate the impact of varied sampling rates on digital relay operating time. Interestingly, investigations show that operating time does not decrease (improve) with increase in sampling rate.…”
Section: Choice Of Appropriate Sampling Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In earlier literature by Venkatesh and Swarup (2012), a total of 16, 24, 32 and 64 samples per cycle of the fundamental frequency (50 Hz) are considered to investigate the impact of varied sampling rates on digital relay operating time. Interestingly, investigations show that operating time does not decrease (improve) with increase in sampling rate.…”
Section: Choice Of Appropriate Sampling Ratementioning
confidence: 99%
“…Wavelet transform based current and/or voltage signal decomposition for fault detection in presence of power swings is reported by Brahma (2007), Alsyoufi and Hajjar (2019), Hajjar (2013) with other applications of wavelet transform presented in Zheng-You et al (2006), Bousaleh et al (2009), Williams and Amaratunga (1994) and Zhu et al (1997). Other studies reported a differential power-based approach using auto regression technique by Venkatesh and Swarup (2012) and frequency components of three phase active power by Rao and Pradhan (2012) and Mahamedi and Zhu (2012) for fault identification during power swings.…”
Section: Introductionmentioning
confidence: 99%
“…Various synthetic, simulated and real-world signals are considered for this study. The fundamental frequency (f ) for all test cases is 50 Hz and the sampling frequency for synthetic signals is 2500 Hz which is typically the used in some low-end protective relays [30]. In all the case studies, top plot shows the signal, middle plot shows the ATSW, and bottom plot shows the estimated frequency.…”
Section: Performance Analysis Of Atsw Based Frequency-estimationmentioning
confidence: 99%
“…• F: It is a set of failure mode nodes that represent physical faults such as phase to phase and phase to ground. (Venkatesh & Swarup, 2012). We consider 30 milliseconds to be upper threshold on the failure propagation time interval, as shown in figure.…”
Section: Tfpg Modelmentioning
confidence: 99%